El Estudio Flexner y una evaluación independiente de los postgrados de medicina: The Flexner Study and an independent evaluation of medical graduate degrees (Revista Médica Hondureña, 2020)
José Ranulfo Lizardo Barahona,1 José Edmundo Lizardo Wildt.2